Autorzy:Elżbieta Jabłońska, Maria Mędrzycka
Wydawnictwo:Nowa Era
Rok wydania:2016
Uprość wyrażenie4.5 gwiazdek na podstawie 8 opinii

`a)` 

`abc(10abc+1)+abc(1-10abc)=ul(10a^2b^2c^2)+ul(ul(abc))+ul(ul(abc))-ul(10a^2b^2c^2)=2abc` 

 

Obliczamy wartość liczbową wyrażenia:

`2abc=2*(-4)*2,5*(-5)=2*2,5*(-4)*(-5)=5*20=100` 

 

 

`b)` 

`4sqrta*sqrtb(sqrt(ab)-1)-sqrt(ab)(sqrta*sqrtb+4)=4sqrt(ab)(sqrt(ab)-1)-sqrt(ab)(sqrt(ab)+4)=` 

`=4sqrt(ab)^2-4sqrt(ab)-sqrt(ab)^2-4sqrt(ab)=ul(4ab)-ul(ul(4sqrt(ab)))-ul(ab)-ul(ul(4sqrt(ab)))=3ab-8sqrt(ab)` 

 

Obliczamy wartość liczbową:

`3ab-8sqrt(ab)=3*3*12-8sqrt(3*12)=108-8sqrt36=108-8*6=108-48=60`